Scheduling algorithm at a switching node - Fu, Jianyun. (2008)
In this dissertation, we will introduce a framework of the current Internet Quality of Service (QoS). The framework includes the Integrated Services/RSVP model, the differentiated Services model, Multip-Protocol Label Switching, Traffic Engineering and Contraint Based Routing.